Cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline and application of cobalt-based polyacid catalyst
Through cobalt-based polyacid catalyst and ultrasonic assisted technology, the aniline oxidation coupling reaction is carried out under low temperature and low pressure conditions, which solves the harsh reaction conditions and catalyst problems in the existing technology, and achieves efficient and environmentally friendly preparation of azobenzene.
Patent Information
- Application Number
- CN202411491992.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the conditions of the aniline oxidation coupling reaction are harsh, there are many by-products, the catalyst is expensive, the activity is low, the selectivity is poor, and it is difficult to recover and reuse.
Develop a cobalt-based polyacid catalyst [H3(DETA)]4{Co[Mo6O12(PO4)2(OH)3(HPO4)2}·8H2O, combined with ultrasonic assistive technology, aniline is carried out at lower temperatures and pressures. Oxidation coupling reaction.
Under mild conditions, the oxidation coupling reaction efficiency of aniline is significantly improved, the yield and purity of azobenzene is improved, energy consumption and production costs are reduced, environmental pollution is reduced, and a more environmentally friendly catalyst system is provided.
Smart Images

Figure CN119285477A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cobalt-based polyacid catalyst for preparing azobenzene through oxidative coupling of aniline and application thereof. Background Art
[0002] Azobenzene, chemical formula is C 12 H 10 N2 is an important organic compound with unique physical and chemical properties. It is mainly used to prepare biphenyl dyes and rubber accelerators, and has broad application prospects in the fields of photoresponsive systems, photoactuators and other light-controlled materials.
[0003] The traditional synthesis method of azobenzene is mainly obtained by the oxidative coupling reaction of aniline, but this method has the following problems: 1) The reaction conditions are harsh, requiring high temperature and high pressure, and a variety of by-products are easily produced during the high temperature and high pressure reaction process, and the product conversion rate and purity are low. 2) The solvents and catalysts used are potentially toxic. 3) The catalysts used are expensive, low in activity, poor in selectivity, and difficult to recover and reuse. Therefore, it is urgent to develop a catalyst with high catalytic activity and good selectivity for the oxidative coupling of aniline to prepare azobenzene. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a cobalt-based polyacid catalyst for preparing azobenzene through oxidative coupling of aniline and its application. The catalyst has excellent catalytic activity, high product selectivity and good stability. The catalyst can carry out oxidative coupling reaction of aniline at lower temperature and pressure in combination with ultrasonic assistance.
[0005] The technical solution of the present invention is:
[0006] A cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline, the molecular formula of the catalyst is as follows:
[0007] [H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O
[0008] Among them, DETA is diethylenetriamine.
[0009] A method for synthesizing a cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline, the specific steps of which are as follows:
[0010] CoCl2·6H2O, Na2MoO4·2H2O, diethylenetriamine (DETA) and H3PO4 were added to deionized water in a molar ratio of 0.85:2.4:9.2:12 and stirred evenly. The pH was adjusted to 1.52 with NaOH solution, poured into a stainless steel reactor, and hydrothermally reacted at 160°C for 4 days. After washing and drying, a reddish-brown blocky crystalline cobalt-based polyacid catalyst was obtained.
[0011] Furthermore, the volume ratio of the diethylenetriamine to deionized water is 1:5.
[0012] Furthermore, the concentration of the NaOH solution is 1 mol·L –1 .
[0013] The cobalt-based polyacid catalyst is used for ultrasound-assisted catalytic oxidative coupling of aniline to prepare azobenzene, and exhibits excellent aniline conversion rate and high azobenzene selectivity.
[0014] The specific steps of the ultrasonic-assisted catalytic selective oxidation of aniline are as follows:
[0015] The cobalt-based polyacid catalyst powder [H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O, substrate aniline and 30% by mass of hydrogen peroxide were added into a 10 mL reaction container, followed by the addition of a solvent, and after being fully mixed, the mixture was fully mixed in a sealed reaction container, and subjected to ultrasonic-assisted catalytic reaction at 45°C for 12 h to obtain azobenzene.
[0016] Furthermore, when the solvent is methanol, a co-catalyst is added, which is Na2S2O8, wherein the cobalt-based polyacid catalyst [H3(DETA)]4{Co[Mo6O 12 The molar ratio of (PO4)2(OH)3(HPO4)2]2}·8H2O (12 mg, 0.4 mmol%): substrate aniline (93 μL, 1 mmol): 30% hydrogen peroxide (5.1 mmol): co-catalyst Na2S2O8 (0.1 mmol) is 4.0×10 -3 :1:5.1:1×10 -1 .
[0017] Furthermore, the solvent is acetic acid and acetonitrile in a volume ratio of 3:7, and the molar ratio of the cobalt-based polyacid catalyst (0.33 mmol%): 30% hydrogen peroxide (4.4 mmol) by mass: substrate aniline (93 μL, 1 mmol) is 3.3×10 -3 :4.4:1.
[0018] Furthermore, the ultrasonic power is 200W and the ultrasonic frequency is 40KHz.
[0019] The beneficial effects of the present invention are:
[0020] (1) Optimizing reaction conditions: The present invention introduces ultrasound-assisted technology to achieve efficient oxidative coupling reaction of aniline under mild conditions. This not only greatly reduces energy consumption and production costs, but also significantly improves the safety of operations, providing new ideas for green chemical processes.
[0021] (2) Innovative catalyst system: The present invention has developed a new catalyst system that exhibits excellent activity and selectivity under ultrasound-assisted conditions, effectively promoting the oxidative coupling process of aniline, greatly improving the yield and purity of azobenzene, and providing a new direction for catalyst design.
[0022] (3) Reduce environmental pollution: In view of the potential environmental hazards of solvents and catalysts in the prior art, the present invention proposes a more environmentally friendly solution. The precious metal catalysts and high temperature conditions used in traditional reactions are effectively replaced, reducing the negative impact on the environment and embodying the concept of green chemistry.
[0023] At present, most of the research on catalytic aniline oxidation reaction focuses on optimizing the aniline reaction efficiency by adjusting conditions such as reaction temperature and solvent. The present invention adopts an ultrasonic method. Ultrasonic waves can not only provide additional energy, but also promote collisions between molecules through mechanical vibration, thereby significantly improving the aniline reaction rate. The results show the high efficiency of the ultrasound-assisted method in catalyzing the selective oxidation reaction of aniline. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the synthesis process of Example 1 of the present invention;
[0025] Figure 2 is the powder X-ray diffraction pattern of Example 1 of the present invention;
[0026] Figure 3 is a coordination environment diagram and a one-dimensional chain structure diagram of Example 1 of the present invention;
[0027] Figure 4 is the infrared spectrum of Example 1 of the present invention;
[0028] Figure 5 is a thermogravimetric graph of Example 1 of the present invention;
[0029] Figure 6 is the X-ray photoelectron energy spectrum of Example 1 of the present invention;
[0030] Figure 7 is a UV-Vis spectrum and band gap value curve diagram of Example 1 of the present invention;
[0031] Figure 8 is a transient photocurrent response curve diagram of Example 1 of the present invention;
[0032] Fig. 9 is a Mott-Schottky diagram of Example 1 of the present invention;
[0033] Fig.10 Schematic diagram of the process of ultrasound-assisted catalytic oxidation of aniline in Example 1 of the present invention;
[0034] Fig.11 is a kinetic study diagram of Example 1 of the present invention;
[0035] Fig.12 is a bar graph of cyclic stability of Example 1 of the present invention;
[0036] Fig.13 1 is the PXRD pattern before and after the cycle of Example 1 of the present invention;
[0037] Fig.14 It is the infrared spectrum before and after the cycle of Example 1 of the present invention. DETAILED DESCRIPTION
[0038] Example 1 Synthesis of [H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O
[0039] like Figure 1 As shown, Na2MoO4·2H2O (0.5 g, 2.4 mmol), CoCl2·6H2O (0.2 g, 0.85 mmol), diethylenetriamine DETA (1.0 mL, 9.2 mmol), H2O (5 mL) and H3PO4 (1 mL, 12 mmol) were stirred for 1.5 h to mix well. –1 The NaOH solution was adjusted to pH 1.52 and placed in a 25 mL polytetrafluoroethylene-lined stainless steel autoclave. After heating at 160 °C for four days, it was cooled to room temperature to obtain reddish brown crystals, which were washed with deionized water and dried at room temperature to obtain reddish brown blocky crystalline cobalt-based polyacid catalyst [H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O, wherein DETA is diethylenetriamine; the yield is 52%, and its powder X-ray diffraction spectrum (PXRD) is as follows Figure 2 As shown, its coordination environment diagram is as follows Figure 3 shown.
[0040] 1. Characterization of the cobalt-based polyacid catalyst according to Example 1 of the present invention
[0041] (1) Powder X-ray diffraction characterization of phase purity
[0042] The prepared sample catalyst was characterized by a powder X-ray diffractometer of Rigaku Ultima IV, Japan. The radiation source was Cu-Kα, the scanning range was 2θ=5-50°, and the scanning speed was 2° / min, to analyze the structure and crystal phase composition of the material. Figure 2 The PXRD spectrum of Example 1 shown shows a high consistency between the experimental value and the simulation value, which indicates that Example 1 has a higher phase purity.
[0043] (2) Characterization of phase composition by infrared spectroscopy
[0044] The prepared catalyst samples were characterized using a Varian 640 FT-IR Fourier transform infrared spectrometer with a wavelength range of 500-4000 cm -1 , the sample and potassium bromide are evenly mixed, with a mass ratio of 1:100. Figure 4 As shown, at 610-745cm -1 The characteristic peaks in the range are attributed to the stretching vibration of ν(Mo-O-Mo); 954cm -1 The characteristic peak at 1040 cm is attributed to the stretching vibration of ν(Mo=O). -1 The characteristic peaks near 1383cm are attributed to ν(P–O). -1 and 1650cm -1 The characteristic peaks at 3225 and 3435 cm are attributed to the stretching vibration of ν(CH) and ν(CN) of DETA. -1 The broad absorption peaks at are due to the stretching vibrations of ν(NH) and ν(OH), which further confirms the structural composition of Example 1.
[0045] (3) Thermogravimetric characterization of the stability of the cobalt-based polyacid catalyst of Example 1
[0046] Thermogravimetric analysis (TGA) was performed using a Hitachi TG / DTA7200 analyzer in a N2 atmosphere at a temperature of 30-800°C and a heating rate of 10°C / min. Figure 5 As shown, the TGA curve shows that the cobalt-based polyacid catalyst of Example 1 undergoes a three-step weight loss process. The first mass loss at 30-155°C is attributed to the loss of 7 water molecules. At 273-417°C, the second mass loss can be attributed to the decomposition of 1 water molecule and 3 DETA. The third weight loss from 450-800°C is attributed to 1 DETA and the collapse of the polyacid structure. It further shows that the cobalt-based polyacid catalyst of Example 1 has good thermal stability below 450°C.
[0047] (4) X-ray Photoelectron Spectroscopy Characterization of the Cobalt-Based Polyacid Catalyst of Example 1
[0048] The test was conducted using an Al-Kα excited X-ray photoelectron spectrometer (XPS) at a power of 150 W. In the XPS spectrum of the cobalt-based polyacid catalyst of Example 1, P 2p, Mo 3d and Co 2p signals were clearly detected ( Figure 6 ). The elemental composition and chemical oxidation state of Example 1 were determined by XPS spectra. 2+ and Mo 5+ The presence of helps to improve the catalytic activity.
[0049] 2. Crystal structure determination
[0050] Single crystal X-ray diffraction (SCXRD) data were collected using a Bruker SMART APEXIICCD diffractometer (λ=0.71073A) with Mo Kα radiation. These data were analyzed and accurately corrected by Olex 2 software to determine the crystal structure of Example 1. Specific crystallographic parameters are shown in Table 1:
[0051] Table 1 Crystallographic data
[0052]
[0053]
[0054] 3. Example 1 of the present invention Synthesis of cobalt-containing {P4Mo6} complex as polyacid catalyst ([H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O Cobalt-based polyacid catalyst for ultrasound-assisted catalytic oxidative coupling reaction of aniline
[0055] like Figure 7-9 As shown, solid ultraviolet diffuse reflectance spectroscopy (UV-Vis), transient photocurrent response curve analysis and Mott-Schottky (MS) characterization tests were performed. Figure 7 As shown, Example 1 exhibits broad absorption in the range below 700 nm, indicating that it may become a promising ultrasound-assisted sonoluminescent catalyst. In addition, the band gap energy of Example 1 was calculated to be 2.02 eV. The photocurrent response curve characterization test further confirmed that Example 1 can generate electrons ( Figure 8 ).
[0056] The electrochemical measurements were performed using a CHI-760 electrochemical workstation with a three-electrode system. Platinum and Ag / AgCl were selected as the counter electrode and reference electrode, respectively. Cleaned indium tin oxide glass (ITO) glass was used as the working electrode. A quartz cell with 0.5 mol / L Na2SO4 (pH=6.8) electrolyte was used as the system for measuring transient photocurrent measurement and electrochemical impedance spectroscopy. Mott-Schottky (MS) was measured in 0.5 mol / L Na2SO4 electrolyte solution, and the AC potential frequencies were 1000, 2000, and 3000 Hz, respectively.
[0057] The results of MS test at different frequencies ( Fig. 9 ), the conduction band (CB) potential of Example 1 was determined to be approximately -0.55 V vs. Ag / AgCl (-0.75 V under standard hydrogen electrode (NHE) conditions). The positive slope of the Mott-Schottky curve indicates that Example 1 can be used as an n-type semiconductor material, further indicating that Example 1 has a wide range of light absorption properties and an adjustable band structure, making it an attractive candidate for ultrasonic sonoluminescence catalysis of aniline selective oxidation.
[0058] Example 1 The process of ultrasound-assisted catalytic aniline oxidative coupling reaction is as follows:
[0059]
[0060] 4. In Example 1, hydrogen peroxide with a mass concentration of 30% is used as an oxidant and a certain amount of cobalt-based polyacid catalyst is used to achieve the stepwise oxidation and coupling reaction of aniline
[0061] First, the cobalt-based polyacid catalyst of Example 1 is accurately weighed in a reaction tube, and 3 mL of a solvent is added. Subsequently, aniline is added to the reaction tube, and hydrogen peroxide with a mass concentration of 30% is introduced as an oxidant. Under the action of the cobalt-based polyacid catalyst and an ultrasonic-assisted method (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz), aniline and hydrogen peroxide undergo an oxidation reaction and are rapidly converted into an N-phenylhydroxylamine (C6H5NHOH) intermediate. Subsequently, under continuous ultrasonic assistance and the action of hydrogen peroxide oxidation agent, N-phenylhydroxylamine is further oxidized to nitrosobenzene and finally converted into nitrobenzene. In addition, aniline undergoes a coupling reaction with the nitrosobenzene generated during the oxidation process to generate azobenzene. Phenylhydroxylamine and nitrosobenzene are converted into oxidized azobenzene in a further oxidation reaction, thereby successfully realizing this multi-step oxidative coupling conversion process.
[0062] (A) The ultrasonic-assisted catalytic effect of Example 1 in the selective oxidation reaction of aniline was investigated by regulating different single solvent types.
[0063] With 5.1mmol of hydrogen peroxide with a mass concentration of 30% as an oxidant, 0.40mmol% of the cobalt-based polyacid catalyst of Example 1 was mixed with 3mL of a solvent, and then 1mmol of aniline was added, and an ultrasonic catalytic reaction was carried out at 45°C (ultrasonic power of 200W, ultrasonic frequency of 40KHz) for 12 hours to study the effect of different solvents on the oxidation of aniline (Table 2). The results show that when methanol is used as a solvent, the aniline conversion rate reaches 85.0%, and the selectivity of the product nitrosobenzene is 76.4%; when acetonitrile is used, the reaction conversion rate can reach 98.7%, and the selectivity of the product nitrosobenzene reaches 76.5%. For the aniline oxidation reaction carried out in other solvents (Table 2, sequence numbers 2, 4 and 5), the main products are usually difficult to distinguish, so methanol and acetonitrile are recommended as the preferred solvents.
[0064] Table 2 Screening of aniline oxidation solvents a
[0065]
[0066] [a] During the reaction process, the following steps were followed: first, 0.40 mmol% of the cobalt-based polyacid catalyst of Example 1 was mixed with 3 mL of different types of solvents, then 1 mmol of aniline was added, followed by 5.1 mmol of 30% hydrogen peroxide, and the reaction system was subjected to ultrasound-assisted catalysis at 45°C for 12 hours (ultrasonic power of 200 W, ultrasonic frequency of 40 kHz) to explore the effects of different solvents on the oxidation reaction of aniline.
[0067] The addition of a reaction promoter can significantly improve the reaction process, increase the dispersion of the catalyst, and reduce the reaction energy barrier. Considering that when methanol and acetonitrile are used as solvents, the main product of the conversion of aniline is nitrosobenzene, and its selectivity can reach 76.4% and 76.5%, respectively. As shown in Tables 3 and 4, acetonitrile and methanol were used as solvents, and a series of additives (such as Na2S2O8 and Na2SO3, etc.) were added to explore the effect of the oxidative coupling reaction of aniline. Among them, when the promoter Na2S2O3 was used in the acetonitrile solvent, 71.5% of the product azobenzene was obtained; when Na2S2O8 was added to the methanol solvent, the conversion rate and product azobenzene selectivity of the ultrasonic catalytic oxidative coupling of aniline reached 99.9%.
[0068] Table 3 Screening of additives for ultrasound-assisted catalytic oxidative coupling of aniline in acetonitrile solvent a
[0069]
[0070] [a] The process conditions are as follows: First, 0.40 mmol% of the cobalt-based polyacid catalyst of Example 1 was mixed with 0.1 mmol of different co-catalysts, and then 3 mL of acetonitrile was added as a solvent, and then 1 mmol of aniline and 5.1 mmol of 30% hydrogen peroxide were added. The above mixture was subjected to an ultrasound-assisted catalytic reaction (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz) at 45° C. for 12 hours to study the effects of different co-catalysts on the oxidation of aniline in acetonitrile solvent.
[0071] Table 4 Screening of additives for ultrasound-assisted catalytic oxidative coupling of aniline in methanol solvent a
[0072]
[0073]
[0074] [a] Process conditions: First, 0.40 mmol% of the cobalt-based polyacid catalyst of Example 1 was mixed with 0.1 mmol of different co-catalysts, followed by the addition of 3 mL of methanol as solvent, 1 mmol of aniline as substrate, and 5.1 mmol of 30% hydrogen peroxide. The above mixture was subjected to ultrasound-assisted catalytic reaction at 45° C. for 12 hours (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz) to study the effects of different co-catalysts on the oxidation of aniline in methanol solvent.
[0075] The effect of ultrasound-assisted catalytic oxidative coupling reaction of aniline was further explored using 30% mass concentration of hydrogen peroxide as an oxidant. The results showed that in methanol solvent, when the amount of hydrogen peroxide reached 5.1 mmol, the aniline conversion rate reached 99.9% (Table 5).
[0076] Table 5 Screening of oxidant dosage for ultrasound-assisted catalytic oxidative coupling of aniline in methanol solvent a
[0077]
[0078] [a] Process: First, 0.40 mmol% of the cobalt-based polyacid catalyst of Example 1, 3 mL of methanol solvent, 0.1 mmol of Na2S2O8 and 1 mmol of aniline were weighed and mixed. Subsequently, different amounts of hydrogen peroxide with a mass fraction of 30% were introduced, and an ultrasound-assisted catalytic reaction was performed at a temperature of 45°C for 12 hours (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz). After the reaction was completed, the product was measured by gas chromatography to analyze the conversion rate of aniline and the selectivity of the product, thereby screening the best catalytic effect of the amount of hydrogen peroxide on the reaction performance.
[0079] Further, under the above optimal conditions, when no catalyst was used, the conversion rate of aniline was 48.4% (Table 6). When 0.40 mmol% of Example 1 was added as a catalyst, after 12 h of ultrasound-assisted catalytic oxidation of aniline, the substrate conversion rate reached 99.9%, indicating that the use of an appropriate amount of catalyst and ultrasound-assisted method can synergistically promote the selective oxidative coupling of aniline.
[0080] Table 6 Screening of the amount of catalyst for ultrasound-assisted catalytic aniline oxidation in methanol solvent a
[0081]
[0082] [a] Process conditions: First, add different masses of the cobalt-based polyacid catalyst of Example 1 in the above table to the reactor, then add 3 mL of methanol solvent, and then add 0.1 mmol of Na2S2O8 and 1 mmol of aniline and 5.1 mmol of hydrogen peroxide with a mass fraction of 30%. The mixture is subjected to ultrasound-assisted catalytic reaction (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz) at 45° C. for 12 hours to promote the conversion of aniline and the formation of the target product. Finally, the product is measured and analyzed by gas chromatography.
[0083] In methanol solvent, with Na2S2O8 as a co-catalyst, the effect of reaction time on ultrasound-assisted catalytic oxidation of aniline was investigated. By shortening the reaction time, when the reaction time was shortened to 10h, 8h and 6h, the conversion rate of aniline was significantly reduced, but the selectivity for the product azobenzene was moderate to good (Table 7), further indicating that 12h is the optimal reaction time.
[0084] Table 7 Screening of aniline oxidation reaction time in methanol solvent a
[0085]
[0086] [a] Process flow: First, accurately weigh 0.40mmol% of the cobalt-based polyacid catalyst of Example 1 and mix it with 3mL of methanol solvent, then add 1mmol of aniline, 0.1mmol of Na2S2O8 and 5.1mmol of hydrogen peroxide with a mass fraction of 30%. Subsequently, the catalytic reaction was carried out at 45°C using ultrasound-assisted catalysis (ultrasonic power of 200W, ultrasonic frequency of 40KHz), and the conversion rate and product selectivity of aniline were explored by controlling different reaction times. After the catalytic reaction was completed, the conversion rate and selectivity of the reaction were measured by gas chromatography.
[0087] like Fig.10As shown, aniline and the reaction product nitrosobenzene continue to react to obtain azobenzene with higher economic value. In Table 2, when acetic acid is used as the solvent, the conversion rate reaches 100%, but the selectivity of azobenzene increases to 45.1%.
[0088] (ii) The ultrasonic-assisted catalytic effect of Example 1 in the selective oxidation reaction of aniline was investigated by adjusting different ratios of acetic acid and acetonitrile as solvents.
[0089] With 4.4mmol of hydrogen peroxide with a mass concentration of 30% as an oxidant, 0.33mmol% of the cobalt-based polyacid catalyst of Example 1 was mixed with 3mL of a solvent, and then 1mmol of aniline was added, and an ultrasonic catalytic reaction was carried out at 45°C (ultrasonic power of 200W, ultrasonic frequency of 40KHz), and the duration was 12 hours, in order to study the use of mixed solvents of acetic acid and acetonitrile in different proportions to explore the oxidative coupling effect of aniline. As shown in Table 8, when the volume ratio of acetic acid to acetonitrile is 3:7, it is the best solvent, the conversion rate of aniline oxidation reaction is 99.0%, and the selectivity of azobenzene can reach 99.0%.
[0090] Table 8 Effect of ultrasonic catalysis on aniline oxidation in mixed solvents of acetic acid and acetonitrile at different ratios a
[0091]
[0092] [a] Select different volume ratios of acetic acid and acetonitrile mixed solvents in a reaction tube, and then add 0.33mmol% of the cobalt-based polyacid catalyst of Example 1. Then, add 1mmol of aniline and 4.4mmol of 30% hydrogen peroxide to the reaction system. Place the reaction tube at 45°C and use ultrasound-assisted catalysis for 12 hours (ultrasonic power of 200W, ultrasonic frequency of 40KHz) to explore the effects of different mixed solvent ratios on reaction efficiency and products.
[0093] The effect of the amount of Example 1 used in a mixed solvent of acetic acid and acetonitrile with a volume ratio of 3:7 on the ultrasonic-assisted catalytic selective oxidation of aniline was further investigated. In a mixed solvent of acetonitrile and acetic acid, the ultrasonic-assisted reaction was carried out for 12 hours, and when the amount of Example 1 was 0.33 mmol%, the conversion rate of the substrate and the selectivity of azobenzene both reached 99.0% (Table 9, No. 2).
[0094] Table 9 Screening of the amount used in Example 1 of ultrasound-assisted catalytic oxidation of aniline in a mixed solvent of acetic acid and acetonitrile a
[0095]
[0096] [a] First, accurately weigh and add different amounts of the cobalt-based polyacid catalyst of Example 1 into a reaction tube, then add 3 mL of a mixed solvent of acetic acid and acetonitrile with an optimal volume ratio of 3:7, and then add 1 mmol of aniline and 4.4 mmol of hydrogen peroxide with a mass fraction of 30%. The mixture is subjected to ultrasound-assisted catalytic reaction at 45°C for 12 hours (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz) to promote the conversion of aniline and the formation of the target product. Finally, the product is analyzed by gas chromatography.
[0097] The effect of 30% hydrogen peroxide as an oxidant in a mixed solvent of acetic acid and acetonitrile on the reaction was further investigated. As can be seen from Table 10, when the amount of hydrogen peroxide reached 4.4 mmol, the aniline conversion rate reached 99.0%.
[0098] Table 10 Screening of oxidant dosage for oxidative coupling of aniline in a mixed solvent of acetic acid and acetonitrile a
[0099]
[0100]
[0101] [a] First, 0.33 mmol% of the cobalt-based polyacid catalyst of Example 1 and a mixed solvent of acetic acid and acetonitrile in a volume ratio of 3:7 were added, 1 mmol of aniline was added as a substrate, and different amounts of hydrogen peroxide with a mass fraction of 30% in the above table were added. Subsequently, an ultrasonic-assisted method was used to react at a temperature of 45° C. for 12 hours (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz). After the reaction was completed, the product was analyzed by gas chromatography to determine the conversion rate of aniline and the selectivity of azobenzene, thereby screening the best amount of hydrogen peroxide with a mass fraction of 30%.
[0102] Under the above optimized reaction conditions, the reaction time was further adjusted. When the reaction time was 10 h, 8 h, 6 h and 4 h, the selectivity of azobenzene was significantly reduced (Table 11).
[0103] Table 11 Screening of aniline oxidation time in acetic acid and acetonitrile mixed solvent a
[0104]
[0105] [a] Process flow: First, 0.33 mmol% of the catalyst of Example 1 was mixed with 3 mL of a mixed solvent of acetic acid and acetonitrile in a volume ratio of 3:7, followed by the addition of 1 mmol of aniline and 4.4 mmol of 30% hydrogen peroxide. Subsequently, the reaction was carried out at a temperature of 45°C using an ultrasound-assisted catalytic method (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz), and the conversion rate and product selectivity of aniline were investigated by controlling different reaction times. After the catalytic reaction was completed, the conversion rate and selectivity of the reaction were analyzed by gas chromatography.
[0106] Temperature and the use of ultrasound-assisted method are important factors affecting the oxidative coupling reaction of aniline. Under the condition of ultrasound-assisted reaction in methanol solvent, the selectivity of azobenzene was 57.9% (Table 12, No. 2); under the condition of heating at 45°C, the selectivity of azobenzene was 51.4% (Table 12, No. 3). At the same time, under the conditions of heating and ultrasound-assisted reaction, the conversion rate of aniline reached 99.9%, and the selectivity of azobenzene reached 99.9% (Table 12, No. 1). In addition, in a mixed solvent of acetonitrile and acetic acid, when the ultrasound-assisted reaction was carried out for 12 hours, the conversion rate of aniline reached 99.0%, and the selectivity for azobenzene reached 99.0% (Table 12, entry 5).
[0107] Table 12 Comparison of the effects of ultrasonic catalytic selective oxidation of aniline in Example 1 under two solvent conditions a
[0108]
[0109] [a] The process is as follows: under optimized reaction conditions, 1mmol aniline, 0.40mmol% of the cobalt-based polyacid catalyst of Example 1, 0.1mmol of the cocatalyst Na2S2O8, 3mL of methanol and 5.1mmol of 30% hydrogen peroxide are mixed, and the mixture is reacted at 45°C for 12 hours using an ultrasonic-assisted method (ultrasonic power of 200W and ultrasonic frequency of 40KHz); [b] The reaction conditions are 1mmol aniline, 0.33mmol% of the cobalt-based polyacid catalyst of Example 1, 3mL of acetic acid: ethyl acetate, and 1mmol aniline, 0.40mmol% of the cobalt-based polyacid catalyst of Example 1, 0.1mmol of the cocatalyst Na2S2O8, 3mL of methanol and 5.1mmol of 30% hydrogen peroxide. [c] Finally, the further reaction used only 1mmol aniline, 0.33mmol% of the cobalt-based polyacid catalyst of Example 1, 3mL) mixed solvent and 4.4mmol of 30% hydrogen peroxide, and the reaction was carried out at 45°C without ultrasound assistance for 12 hours (ultrasonic power of 200W, ultrasonic frequency of 40KHz).
[0110] Under the optimal conditions in methanol as solvent, comparative experiments were carried out using CoCl2·6H2O, Na2MoO4, DETA and their physical mixtures as catalysts (Table 13). The results show that DETA, Na2MoO4 and CoCl2·6H2O as homogeneous catalysts exhibit certain catalytic activity for the oxidation reaction of aniline (Table 13, No. 2, 3 and 4). In addition, a simple physical mixture of CoCl2·6H2O, Na2MoO4 and DETA was subjected to a control experiment (Table 13, No. 5). By comparing the results, it was found that the conversion rate of the oxidation reaction of aniline catalyzed by the physical mixture was not satisfactory. Example 1 shows excellent catalytic activity, which may be attributed to the {P4Mo6} material as the catalytic active center and Co 2+ Synergistic effects between ions.
[0111] Table 13 Effect of catalyst type on reaction in methanol solvent a
[0112]
[0113]
[0114] [a] Process: Under ultrasound-assisted conditions, first accurately weigh the precursor (0.40 mmol%) of the synthetic cobalt-based polyacid catalyst into a reaction tube, then add 0.1 mmol of Na2S2O8, 3.0 mL of methanol, 1.0 mmol of aniline and 5.1 mmol of 30% hydrogen peroxide in sequence. The reaction system is reacted at 45°C for 12 hours under ultrasound-assisted conditions (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz). After the reaction is completed, the conversion rate and selectivity of the reaction are measured by gas chromatography.
[0115] like Fig.11 As shown, the ln(C t / C0) has a linear relationship, which is consistent with the pseudo-first-order kinetic model. The kinetic constant of the pseudo-first-order reaction is 0.3038h -1 .
[0116] V. Repeated use stability of the cobalt-based polyacid catalyst of Example 1 of the present invention
[0117] To ensure the activity and purity of the catalyst, after the first ultrasonic-assisted catalytic reaction, the catalyst was washed 3 to 4 times with 20 mL of methanol. After washing, the cobalt-based polyacid catalyst was placed in a vacuum oven and dried overnight at 60°C. After the catalyst was completely dried, it was added to a reaction tube, and 0.1 mmol Na2S2O8, 3.0 mL of methanol, 1.0 mmol of aniline and 30% by mass of hydrogen peroxide were added at a time to carry out a new round of ultrasonic-assisted catalytic aniline oxidative coupling reaction (ultrasonic power of 200 W, frequency of 40 KHz). After five cycles of the above-mentioned reaction, the conversion rate and product selectivity of the cobalt-based polyacid catalyst in Example 1 in the ultrasonic-assisted catalytic aniline oxidative coupling reaction did not decrease significantly, proving its good stability. ( Fig.12 ).
[0118] like Fig.13 and Fig.14 As shown, the catalyst powder after the cycle experiment was characterized and tested by PXRD and FT-IR, which further proved the stability of the cobalt-based polyacid catalyst of Example 1 before and after the cycle reaction.
[0119] VI. Example 1 Effect of Ultrasonic Catalytic Selective Oxidative Coupling of Aniline Derivatives
[0120] According to the stability of the cobalt-based polyacid catalyst of Example 1, the substrate range of the oxidation reaction system was further tested under the optimal reaction conditions when methanol was used as the solvent. Under the optimized reaction conditions, the methyl-substituted derivatives had good conversion and selectivity for the corresponding azobenzene products (Table 14, sequence numbers 2-3). The comparative study results showed that substrates with electron-donating groups (-Me, -OMe) had higher activity than substrates containing electron-withdrawing groups (-F, -Cl and -Br), which may be related to the electronic properties of the substituents on the aromatic ring. In addition, the electron-donating substituents seemed to be less affected by the steric hindrance effect, where the substituents were located at the ortho position, and the meta and para positions could also produce the corresponding azobenzene derivatives with a higher conversion rate. However, compared with the meta-substituent products, the reaction yields of the para-substituent products were much higher (Table 14, sequence numbers 4 and 8). In particular, the parallel substrates of aniline substituted with p-butyl and p-isopropyl were converted into azobenzene derivatives, and the reaction selectivities were 76.7% and 89.0% respectively (Table 14, sequence numbers 5-6).
[0121] Table 14 Effect of ultrasound-assisted catalytic oxidative coupling of aniline derivatives in methanol solvent
[0122]
[0123]
[0124]
[0125]
[0126] [a] Process conditions: First, 0.40 mmol% of the cobalt-based polyacid catalyst of Example 1 was mixed with 0.1 mmol of Na2S2O8 as a cocatalyst, followed by the addition of 3 mL of methanol as a solvent, 1 mmol of different aniline derivatives as substrates, and 5.1 mmol of 30% hydrogen peroxide. The above mixture was subjected to ultrasound-assisted catalytic reaction at 45° C. for 12 hours (ultrasonic power of 200 W, ultrasonic frequency of 40 KHz) to study the effect of the cobalt-based polyacid catalyst of Example 1 on the oxidative coupling of different aniline derivatives in methanol solvent.
[0127] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline, characterized in that: The molecular formula of the catalyst is as follows: [H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O; Among them, DETA is diethylenetriamine.
2. The method for synthesizing a cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline according to claim 1, characterized in that: The specific steps are as follows: CoCl2·6H2O, Na2MoO4·2H2O, diethylenetriamine (DETA) and H3PO4 were added to deionized water in a molar ratio of 0.85:2.4:9.2:12 and stirred evenly. The pH was adjusted to 1.52 with NaOH solution, poured into a stainless steel reactor, and hydrothermally reacted at 160°C for 4 days. After washing and drying, a cobalt-based polyacid catalyst was obtained.
3. The method for synthesizing a cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline according to claim 2, characterized in that: The volume ratio of the diethylenetriamine to deionized water is 1:
5.
4. The method for synthesizing a cobalt-based polyacid catalyst for preparing azobenzene by oxidative coupling of aniline according to claim 2, characterized in that: The concentration of the NaOH solution is 1 mol·L -1 .
5. Use of the cobalt-based polyacid catalyst as claimed in claim 1 in catalyzing the oxidative coupling of aniline to prepare azobenzene.
6. Use of the cobalt-based polyacid catalyst according to claim 5 as a catalyst for preparing azobenzene by oxidative coupling of aniline, characterized in that: Azobenzene was prepared by ultrasound-assisted selective oxidative coupling of aniline.
7. Use of the cobalt-based polyacid catalyst according to claim 5 as a catalyst for preparing azobenzene by oxidative coupling of aniline, characterized in that: specific Here are the steps: Cobalt-based polyacid catalyst powder [H3(DETA)]4{Co[Mo6O 12 (PO4)2(OH)3(HPO4)2]2}·8H2O, substrate aniline and 30% by mass of hydrogen peroxide were added into a 10 mL reaction container, followed by the addition of a solvent, and after being fully mixed, the mixture was fully mixed in a sealed reaction container, and subjected to ultrasonic-assisted catalytic reaction at 45°C for 12 h to obtain azobenzene.
8. Use of the cobalt-based polyacid catalyst according to claim 7 in catalyzing the oxidative coupling of aniline to prepare azobenzene, characterized in that: When the solvent is methanol, a co-catalyst is added, which is Na2S2O8. The molar ratio of cobalt-based polyacid catalyst: aniline: 30% hydrogen peroxide: Na2S2O8 is 4.0×10 -3 :1:5.1:1×10 -1 .
9. Use of the cobalt-based polyacid catalyst according to claim 7 in catalyzing the oxidative coupling of aniline to prepare azobenzene, characterized in that: The solvent is acetic acid and acetonitrile in a volume ratio of 3:7, and the molar ratio of the cobalt-based polyacid catalyst: 30% hydrogen peroxide: aniline is 3.3×10 -3 :4.4:
1.
10. Use of the cobalt-based polyacid catalyst according to claim 7 in catalyzing the oxidative coupling of aniline to prepare azobenzene, characterized in that: The ultrasonic power is 200W, and the ultrasonic frequency is 40KHz.